'Short Interest Pressure' and Competitive Behaviour. (27th April 2016) - Hughes‐Morgan, Margaret; Ferrier, Walter J.
Abstract : This study introduces and examines a new‐to‐strategy form of Wall Street pressure – 'short interest pressure' – the tension felt by management caused by short sales of the firm's stock. Drawing from a sample of over 5000 competitive actions carried out by competing firms over a 6‐year time period, we test whether the level of short interest pressure experienced by the firm in one time period is predictive of properties of the firm's competitive action repertoire in the ensuing time period. Our findings suggest that when faced with short interest pressure firms tend to carry out a higher number of competitive actions in the following time period, as well as a set of actions that deviate from the industry norm. In addition, post hoc analysis reveals that this effect is amplified for poorly performing firms. Thus, our study contributes to a deeper understanding of the relationship between capital market signals and competitive strategy.